Living the puerperium: womens’ testimonials - Eduardo, Kylvia Gardênia Torres; Barbosa, Régia Christina Moura; Antero, Maria de Fátima; Pinheiro, Ana Karina Bezerra (Rev Rene, 2005)
That study aims at understanding how women live the puerperal period. It is an exploratory, descriptive, and qualitative study. It was developed with ten women in the puerperium registered in the Training Center in Primary Attention in Fortaleza. The collection of data was performed through home visits. The data were grouped into two categories: Positive Aspects, and Negative Aspects of Puerperium. The participants’ ages ranged from 15 to 42 years-old, being more than half single and primiparae. The predominant level of education was primary school (4 women) and high school (4 women). All of them were in the late puerperium. The positive reports were associated with the support offered in that period, which consequently turned life easier and helped them solve some problems. The participants highlighted as negative aspects of the puerperium: complications in the puerperium and difficulties in assuming the role of mother. We observed the importance of the social support network, mainly of the nursing care, which should be humanized and offered to everybody in order to give all women conditions for an effective puerperal adaptation.